Prospective comparative study of endoscopic submucosal dissection and gastrectomy for early neoplastic lesions including patients’ perspectives - Libânio, Diogo; Braga, Vânia; Ferraz, Sílvia; Castro, Rui; Lage, Jorge; Pita, Inês; Ribeiro, Cátia; Abreu De Sousa, Joaquim; Dinis-Ribeiro, Mário; Pimentel-Nunes, Pedro (Endoscopy, 2019)
Background There are no prospective studies comparing endoscopic submucosal dissection (ESD) and gastrectomy, especially evaluating patient-reported outcomes. Our aim was to compare the safety and impact on quality of life (QoL) of ESD and gastrectomy in patients with early gastric neoplasia. Methods This prospective study included consecutive patients presenting with early gastric neoplasia in a tertiary center from January 2015 to August 2016. Data collection included curative resection, adverse events (AEs), and patient-reported outcomes (questionnaires: EORTC QLQ-C30, EORTC STO-22, EQ-5D-5 L, and Assessment of Survivor Concerns) before and after interventions (after 1 month, 3 – 6 months, and 1 year). Results 254 patients with early lesions were included: 153 managed by ESD and 101 by gastrectomy, the former being significantly older and with less advanced lesions. Mean procedural time and length of stay were significantly higher in the surgery group (164 vs. 72 minutes and 16.3 vs. 3.5 days; P < 0.001). Complete resection was higher in the surgical group (99 % vs. 90 %; P = 0.02); ESD was curative in 79 % of patients. Severe AEs and surgical re-intervention were significantly more frequent in the gastrectomy group (21.8 % vs. 7.8 % and 11 % vs. 1 %, respectively). Endoscopic treatment was associated with a positive impact on global health-related QoL at 1 year (net difference + 9.9; P = 0.006), role function and symptom scales (fatigue, pain, appetite, eating restrictions, dysphagia, and body image). Concerns about recurrence did not differ between the groups. Conclusions In patients with early gastric neoplasia, ESD is safer and is associated with a positive impact on health-related QoL when compared with gastrectomy, without increasing fear of recurrence and new lesions.